The characteristic study of rotation and elevation technique of solar tracker - Mohd Zul-Fadly, Zainuddin (2009)
Solar tracker is a device at solar panel which the characteristic of this device is it will track the motion of sun across the sky to ensure the amount of sunlight strikes at the solar panel are maximum. Currently, there are two techniques to control the solar tracker which is rotation-elevation technique and azimuthally-elevation technique. A characteristic study on the rotation and elevation tracking technique in solar tracker is proposed. The study will focus on the characteristic of this tracking technique and prove this concept by demonstrating this technique in practical. The characteristic study will base on the parameter in the equation involved in this tracking technique and plotted graph. Several parameters then will be manipulated to see the effect of that parameter to the plotted graph. The process of demonstrating this technique in practical will be made with several considerations. The benefit of this study is that it can help the future research related with this tracking technique to be their reference for their research.